Enhancing breast cancer treatment: mesoporous dopamine nanoparticles in synergy with chrysin for photothermal therapy - Zhu, Jing; Zhang, Heng; Lan, Haomiao; Bi, Bing; Peng, Xianfeng; Li, Dandan; Wang, Haili; Zhu, Ke; Shao, Fuqiang; Yin, Minggang (Frontiers in Oncology, 2024)
Breast cancer is one of the most common types of cancer. A critical component of its treatment involves blocking estrogen, which can be achieved through competitive inhibition of estrogen binding to tumor estrogen receptors, down-regulating estrogen expression in the body, and reducing the expression of estrogen receptors on tumors.Our research indicates that Chrysin may down-regulate estrogen receptor expression in breast cancer, a finding confirmed through network pharmacological analysis and cell experiments. However, the clinical application of natural drugs like Chrysin is hindered by their poor water solubility, which significantly limits their bioavailability.To overcome this challenge, we developed a delivery system using mesoporous dopamine (mPDA) nanoparticles to effectively deliver Chrysin to breast cancer cells. This approach successfully addresses the solubility issue, enhancing Chrysin's potential in cancer treatment. Moreover, due to the light-absorbing properties of mPDA nanoparticles, we explored the synergistic effects of combining photothermal therapy (PTT) with Chrysin. Our study emphasizes the crucial role of PTT in stimulating tumor immunity, thereby amplifying the therapeutic efficacy against breast cancer. This strategy shows promise and has the potential to advance cancer treatment methodologies.